Diseminasi Teknik Klasifikasi Naïve Bayes pada Instrusion Detection System di Perusahaan Artajasa - Teja Endra Eng Tju; Dolly Virgian Shaka Yudha Sakti; Muhammad Kamil Suryadewiansyah (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Artajasa as a real-time online transaction service provider faces the challenge of monitoring transaction traffic and identifying transactions that are allowed or not. This community service activity aims to create a web-based application to help analyze alerts from the detection system that was previously carried out manually. The implementation of activities consists of interviews and observations, data collection and processing, application analysis and design, application testing and implementation. With the Naïve Bayes algorithm, the prediction results from the historical data obtained an accuracy of 0.88 and the results of the User Acceptance Test showed that all functions had been tried and worked well. With the application made, the work of artajasa's security team becomes effective and efficient because there is no need to check every alert data anymore, but simply focus on the results of the difference between the results of predictions and alerts.